PROFIL MISKONSEPSI LISTRIK DINAMIS MENGGUNAKAN THREE-TIER DIAGNOSTIC TEST SKALA GUTTMAN PADA SISWA SMP - Mubammad Ziaul Farihin; Siti Nurul Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Misconceptions in dynamic electricity remain a common issue in physics learning due to the abstract and interrelated nature of its concepts. This study aimed to map the misconception profile of ninth-grade students on dynamic electricity using a three-tier diagnostic test based on the Guttman scale. The research employed a quantitative approach with a descriptive-correlational diagnostic design. The sample consisted of 49 ninth-grade students selected through purposive sampling. The research instrument included 15 items of a three-tier diagnostic test covering five sub-concepts: electric current, voltage, electric circuits, resistance, and Ohm’s law. Data analysis was conducted using descriptive statistics to determine the percentage of students’ response categories and Spearman’s rho correlation analysis to identify relationships among sub-concepts. The results showed that the highest level of misconception occurred in the voltage sub-concept (41%), followed by electric circuits (31.3%), resistance (22.9%), and Ohm’s law (22.2%), while the electric current sub-concept showed the lowest level of misconception (13.2%). Correlation analysis indicated significant positive relationships among several sub-concepts, particularly between voltage and electric circuits as well as resistance. These findings indicate that misconceptions in dynamic electricity are systemic and interrelated across sub-concepts. The use of a Guttman-scale-based three-tier diagnostic test proved effective in identifying misconceptions more accurately. Therefore, the results of this study can serve as an empirical basis for designing instructional strategies aimed at reconstructing students’ conceptual understanding.